Rituximab in patients with primary CNS lymphoma (HOVON 105/ALLG NHL 24): a randomised, open-label, phase 3 intergroup study. Issue 2 (February 2019) - Bromberg, Jacoline E C; Issa, Samar; Bakunina, Katerina; Minnema, Monique C; Seute, Tatjana; Durian, Marc; Cull, Gavin; Schouten, Harry C; Stevens, Wendy B C; Zijlstra, Josee M; Baars, Joke W; Nijland, Marcel; et al.
Summary: Background: The prognosis for primary CNS lymphoma has improved with the use of high-dose methotrexate-based chemotherapy, but patient outcomes remain poor. Rituximab, a chimeric monoclonal antibody that targets the CD20 cell surface protein, has substantial activity in systemic CD20-positive diffuse large B-cell lymphoma, but its efficacy in primary CNS lymphoma is unknown and low penetration of the large rituximab molecule through the blood–brain barrier could limit its effect. We aimed to investigate the addition of rituximab to a high-dose methotrexate-based chemotherapy regimen in patients with newly diagnosed primary CNS lymphoma. Methods: This intergroup, multicentre, open-label, randomised phase 3 study was done at 23 hospitals in the Netherlands, Australia, and New Zealand. Non-immunocompromised patients aged 18–70 years with newly diagnosed primary CNS lymphoma were randomly assigned (1:1) to receive methotrexate-based chemotherapy with or without intravenous rituximab. We used a web-based randomisation system with stratification by centre, age, and Eastern Cooperative Oncology Group–WHO performance status, and a minimisation procedure. All group assignment was open label and neither investigators nor patients were masked to allocation. All patients were treated with two 28-day cycles of induction chemotherapy, consisting of intravenous methotrexate 3 g per m 2 on days 1 and 15, intravenous carmustine 100 mg per m 2 on day 4, intravenous teniposide 100 mg per m 2 on days 2 and 3, and oral prednisone 60 mg per m 2 on days 1–5, with (R-MBVP) or without (MBVP) intravenous rituximab 375 mg per m 2 on days 0, 7, 14, and 21 in cycle one and days 0 and 14 in cycle two. Patients with response at the end of induction subsequently received high-dose cytarabine and, in patients aged 60 years or younger, low-dose whole-brain radiotherapy. The primary endpoint was event-free survival, with events defined as not reaching complete response or complete response unconfirmed at the end of treatment, or progression or death after response; analysis was adjusted for age and performance score. Patients were analysed on a modified intention-to-treat basis. This trial is registered with the Nederlands Trial Register, number NTR2427, and the Australian New Zealand Clinical Trials Registry, number ACTRN12610000908033. The trial was closed on May 27, 2016, after achieving complete accrual, and follow-up is ongoing. Findings: Between Aug 3, 2010, and May 27, 2016, we recruited 200 patients (109 men and 91 women; median age was 61 years [IQR 55–67]). We randomly assigned 100 patients to MBVP and 99 patients to R-MBVP. One patient was randomly assigned to the R-MBVP group but found to be ineligible because of an incorrect diagnosis and was excluded from all analyses. After a median follow-up of 32·9 months (IQR 23·9–51·5), 98 patients had had an event (51 in the MBVP group and 47 in the R-MBVP group), of whom 79 had died (41 in the MBVP group and 38 in the R-MBVP group). Event-free survival at 1 year was 49% (95% CI 39–58) in the MBVP group (no rituximab) and 52% (42–61) in the R-MBVP group (with rituximab; hazard ratio 1·00, 95% CI 0·70–1·43, p=0·99). Grade 3 or 4 adverse events occurred in 58 (58%) patients in the MBVP group and 63 (64%) patients in the R-MBVP group, with infections (24 [24%] patients receiving MBVP vs 21 [21%] patients receiving R-MBVP), haematological toxicity (15 [15%] vs 12 [12%]), and nervous system disorders (ten [10%] vs 15 [15%]) being the most common. Life-threatening or fatal serious adverse events occurred in 12 (12%) patients in the MBVP group and ten (10%) patients in the R-MBVP group, and five (5%) patients in the MBVP group and three (3%) in the R-MBVP group died from treatment-related causes. Interpretation: We found no clear benefit of addition of rituximab to methotrexate, carmustine, teniposide, and prednisone chemotherapy in primary CNS lymphoma. Therefore, the results of this study do not support the use of rituximab as a component of standard treatment in primary CNS lymphoma. Funding: Roche, the Dutch Cancer Society, and Stichting STOPhersentumoren.